Application of statistical analysis for the optimization of mycelia and polysaccharide production by Tremella aurantialba - Zhang, Zhicai (Array, 2007)
Statistical analyses were applied to optimize the medium composition for the mycelial growth and polysaccharide production by Tremella aurantialba in shake flask cultures. Firstly, four significant factors (xylan, peptone, wheat bran and corn powder) on mycelial growth and polysaccharide yield (p≤0.05) were obtained using one-at-a-time design. Subsequently, in order to study the mutual interactions between variables, the effects of these factors were further investigated using four-factor, three-level orthogonal test design and the optimal composition was (in g/L): xylan 40, peptone 10, wheat bran 20, corn powder 20, KH2PO4 1.2 and MgSO4·7H2 O 0.6. Finally, the maximum mycelium yield and polysaccharide production in 50-litre stirred-tank bioreactor reached 36.8 and 3.01 g/L under the optimized medium, respectively